Experimental and analytical sutdy of reinforced concrete interior beam-wide column joints for seismic performance - Wu, Yiming. (2008)
Reinforced concrete structures consisting of wall-like wide column elements are very common in a region of low to moderate seismicity, and are the predominant structural system in Singapore and Malaysia. Recent post-earthquake investigations indicated that extensive damage occurred as a result of excessive shear deformation.